Hubungan Efikasi Diri Dan Kepercayaan Diri Dengan Motivasi Berprestasi Mahasiswa Atlet Maluku Utara - Adam, Syahril (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this research is to reveal the relationship between self-efficacy and self-confidence with the achievement motivation of North Maluku student athletes. The method used is survey research using a questionnaire compiled by the researcher. This research was conducted in North Maluku with the research objects being students who were active as well as athletes and participated in national student events, namely POMNas 2019 and the 2019 Menpora Cup U-21 Student League, totaling 106 athletes. The results of the research show that there is a significant relationship between self-efficacy and achievement motivation which obtained a significance value of 0.000, because the significance level of self-efficacy is smaller than 0.05 (5%), and the relationship between self-confidence and achievement motivation for student athletes obtained a significance value of 0.000, because the significance level of confidence is smaller than 0.05 (5%). Simultaneously, self-efficacy and self-confidence with achievement motivation obtained an F value of 256.093 and a significance value of 0.000 <5%, meaning that there is a significant relationship between the variables of self-efficacy and self-confidence, which together contribute to the achievement motivation of North Maluku student athletes.